2012
DOI: 10.1590/s1679-62252012000300021
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits of juveniles of the Mayan cichlid, Cichlasoma urophthalmus, in mangrove ponds of an offshore islet in Belize, Central America

Abstract: Foraging habitats of juveniles of the Mayan cichlid, Cichlasoma urophthalmus (Günther, 1862), were investigated in two mangrove ponds located in Twin Cays offshore islet in Belize: Sink Hole pond (SH) and Hidden Lake pond (HL). Sink Hole pond is a semiclosed body of water, whereas Hidden Lake pond is connected by a channel to adjacent seagrass beds that surround the islet. Gut contents of 21 juvenile C. urophthalmus (9.8-13.2 cm total length) were analyzed, and five prey taxa were identified. In both mangrove … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…One study in Asia found that O. mossambicus acted as a detrivore, herbivore and carnivore in different lakes in Sri Lanka (De Silva et al 1984). The diet of M. urophthalmus ranged from herbivore, to omnivore, and carnivore depending on sites in their native range in Mexico and Belize (Caso Ch avez et al 1986;Martinez-Palacios and Ross 1988;Ch avez-L ovez et al 2005;Vaslet et al 2012). Bergmann and Motta (2005) reported that M. urophthalmus was an omnivore in south Florida, where this species had been established as an exotic species.…”
Section: Introductionmentioning
confidence: 99%
“…One study in Asia found that O. mossambicus acted as a detrivore, herbivore and carnivore in different lakes in Sri Lanka (De Silva et al 1984). The diet of M. urophthalmus ranged from herbivore, to omnivore, and carnivore depending on sites in their native range in Mexico and Belize (Caso Ch avez et al 1986;Martinez-Palacios and Ross 1988;Ch avez-L ovez et al 2005;Vaslet et al 2012). Bergmann and Motta (2005) reported that M. urophthalmus was an omnivore in south Florida, where this species had been established as an exotic species.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of complex responses to landscape structure are interspecific variation in permeability of culverts to fish movement (MacPherson et al 2012) and variable use of seasonally flooded habitats (Poizat and Crivelli 1997). Both species in the current study are fish predators, native to ecosystems with strong seasonal fluctuations in water level, and have been documented as occupying a wide diversity of habitats (Greenfield and Thomerson 1997;Vaslet et al 2012;Warren 2009). One noticeable difference between Mayan cichlids and Florida largemouth bass is in body size (Table S2 1 ) and could be one of the traits that modified relationships between depth and dispersal (Fig.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, mangrove contributions to fish diets vary depending on the habitat configuration and hydrologic features. This is particularly true for offshore mangrove islets, such as Twin Cays, where fish species from semi‐enclosed mangrove ponds rely on mangrove prey, whereas fishes from fringing mangroves mostly feed in seagrass beds (Vaslet et al, , b; this study). The limited contribution of mangrove prey to fish diets is more likely to be due to the chemical composition of mangrove organic carbon that has low nutritional value and high concentrations of refractory compounds, such as lignin‐derived phenols or tannins (Kristensen et al, ).…”
Section: Discussionmentioning
confidence: 82%